2009
DOI: 10.1080/10286020903367136
|View full text |Cite
|
Sign up to set email alerts
|

Steroids and alkaloids from the South China Sea spongeAxinellasp.

Abstract: A new steroid 24beta-methylcholasta-1,8,14,22,25-penten-3-one-5alpha-ol (1) and a new alkaloid 1-(1H-indol-3-yl)-2,3-dihydroxy-5-methyl-hexane (2), together with four known compounds, were isolated from the EtOH extract of the South China Sea sponge Axinella sp. The structures of 1 and 2 were determined on the basis of extensive spectroscopic analysis, including 1D and 2D NMR spectral data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 9 publications
1
9
0
Order By: Relevance
“…1-(1 H -Indol-3-yl)-2,3-dihydroxy-5-methyl-hexane ( 75 ) was isolated from the South China Sea sponge Axinella sp. ( Figure 16 ) [ 64 ].…”
Section: Marine Indole Alkaloidsmentioning
confidence: 99%
“…1-(1 H -Indol-3-yl)-2,3-dihydroxy-5-methyl-hexane ( 75 ) was isolated from the South China Sea sponge Axinella sp. ( Figure 16 ) [ 64 ].…”
Section: Marine Indole Alkaloidsmentioning
confidence: 99%
“…[21], Axinella sp. [22]. However, to our knowledge, it is the first time that such kind of steroid was found from marine sponge X. testudinaria.…”
Section: Resultsmentioning
confidence: 82%
“…The bioassay result indicated that compound 1 exhibit significant PTP1B inhibitory activity with an IC 50 value of 4.27^0.55 mM, when compared to the positive control oleanolic acid (IC 50 ¼ 2.63^0.22 mM). In addition, cytotoxic activities of 1 against the growth of human promyelocytic leukemia cells (HL60) and human lung adenocarcinoma cells (A549) have also been tested since literature survey revealed that many oxygenated steroids showed promising cytotoxicity against various tumor cell lines [18][19][20][21][22][23]. Unfortunately, the results indicated that 1 was inactive against the above cancer cell lines (50% effective dose of clonal inhibition ED 50 .…”
Section: Resultsmentioning
confidence: 99%
“…Since the first report of steroids from marine sponges by Bergman in 1949 [ 34 ], numerous reports have described conventional and unconventional steroids from demosponges with modifications on the tetracyclic nucleus or the side chain, including e.g., aminosteroids, sulfated polyhydroxysterols, side-chain-oxygenated sterols and sulfated steroid-amino acid conjugates [ 20 , 33 , 35 , 36 , 37 ]. Axinella sponges are known to have generally complex steroid profiles including steroids and nor-steroids [ 36 , 38 , 39 ]. The previous GC-MS study on A. sinoxea led to the identification of eight steroidal compounds: cholesta-5,22-dien-3β-ol, cholest-5-en-3β-ol, ergosta-5,22-dien-3β-ol, ergost-5-en-3β-ol, stigmasta-5,22-dien-3β-ol, γ-sitosterol, 33-norgorgosta-5,24(28)-dien-3β-ol and stigmasta-5,24(28)-dien-3β-ol [ 12 ].…”
Section: Discussionmentioning
confidence: 99%